2022
DOI: 10.3390/ijms23126608
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Buffer Capacity of Polyelectrolyte Microcapsules Depending on Their Ionic Environment and Incubation Temperature

Abstract: Polyelectrolyte microcapsules (PMCs) are used in the development of new forms of drugs, coatings and diagnostic systems. Their buffer capacity, depending on the conditions of the medium, has not been practically studied, although it can affect the structure of both the capsule itself and the encapsulated agents. In this connection, we studied the buffer capacity of polyelectrolyte microcapsules of the composition (polystyrene sulfonate/polyallylamine)3 ((PSS/PAH)3) depending on the concentration and the type o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Additionally, we found the dependence of the buffer capacity’s behavior on the PMC shell’s composition, the presence of an encapsulated protein, the magnitude of ionic strength, and the temperature of the solution. These studies demonstrated that the buffer properties of microcapsules are determined by the charged regions of PAH (uncompensated with PSS) in the composition of their shell [ 2 , 9 ]. However, as described above, the number and density of PAH charged groups (distance between nearest groups of -NH 3 + groups) also depend on the number of microcapsule shell layers and the number of microcapsules themselves.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we found the dependence of the buffer capacity’s behavior on the PMC shell’s composition, the presence of an encapsulated protein, the magnitude of ionic strength, and the temperature of the solution. These studies demonstrated that the buffer properties of microcapsules are determined by the charged regions of PAH (uncompensated with PSS) in the composition of their shell [ 2 , 9 ]. However, as described above, the number and density of PAH charged groups (distance between nearest groups of -NH 3 + groups) also depend on the number of microcapsule shell layers and the number of microcapsules themselves.…”
Section: Resultsmentioning
confidence: 99%
“…Dubrovsky et al demonstrated the buffer capacity of polyelectrolyte microcapsules and the dependence of the behavior of the buffer capacity on the presence of an encapsulated protein [ 2 ], the ionic strength, and the temperature of the solution [ 9 ]. Additionally, these works confirmed that the buffer properties of microcapsules are determined by polyallylamine (PAH) sites uncompensated with polystyrene sulfonate in the composition of a PMC’s shell.…”
Section: Introductionmentioning
confidence: 99%
“…The third component was a single layer of polyamine adsorbed from the dispersion— in one case this was polyallylamine (purchased from Merck KGaA, Darmstadt, Germany; the resulting membrane is denoted as MK-40-M-PAH) and in the other case it was polyethylenimine (purchased from Merck KGaA, Darmstadt, Germany; the resulting membrane is denoted as MK-40-M-PEI). Polyallylamine is used for layer-by-layer assembly [ 39 ] as a component of new promising materials (such as thermo-responsive polymers with cleavage-induced phase transition [ 40 ] or coatings decomposing by application of electric potential [ 41 ]), including biomedical applications such as creation of nano-capsules for drug delivery [ 42 ] and food packaging [ 43 ]. Polyethylenimine is frequently used as a polymer carrier [ 44 ] and basis for loading of nanoparticles [ 45 ] or coating for medical applications [ 46 ].…”
Section: Methodsmentioning
confidence: 99%